(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Whether people own dogs, cats, birds, reptiles, rabbits or fish, they need to be aware that domestic animals can have an effect on their health by transmitting certain diseases. Animal diseases, that are zoonotic diseases, are those naturally transmitted from vertebrate animals to humans. The aim of the research was to explore the perceptions of the local Grenadian public about their knowledge towards certain zoonotic diseases. In Grenada, there are known reservoirs for zoonotic diseases in the form of rabies from stray dogs and mongoose. Rabies is a fatal viral disease that infects the brain and spinal cord in mammals including humans. The virus is transmitted through the saliva of a rabid animal, usually by a bite. The study population comprised adults, non-health professional, Grenadian citizens in the parish of St. George. A total of 450 participants comprised the sample base for the collected data. Rabies was correctly identified as being caused by a virus among 28.4% of the sample population. Rabies as obtained from the bite of an infected animal was correctly identified by 434 (96.4%) of participants. Knowledge of the mongoose as the animal reservoir of Rabies in Grenada was correctly recognized by 434 (96.4%) of the participants. Rabies prevention, requiring vaccination of animals, was identified by 339 (75.3%) of the study population. For Rabies, 20 (4.4%) of the population selected nervous reactions as the associated symptom.